(untitled) (International Conference on Computers in Education, 2011)
We have developed an intelligent educational system for high school chemistry, named Intelligent Practice Supporting System (IPSS). Exercise problems that existing IPSS can handle are designed independently of each other problems. However, teachers often design a set of problems that has a certain educational effect; for example, learners can focus difference of two materials by solving two problems on each of the materials. We call such set of problems “related problem set (RPS)”. To design RPS is not so easy task for teachers. In this paper, we propose a method to generate RPSs by transforming representations of problem solving process of an original problem. We add this function to IPSS, and extend IPSS to be able to propose an additional exercise using generated RPS.